The Janus Corner - E. Czerwin´ ska, Monika; N. Timmermann, Barbara; Tomczyk, Michal (Pharmacognosy Communications)
The scientifi c program included plenary sessions dedicated primarily to prestigious award lectures and a celebration of the 75 th Volume of the ASP’s fl agship journal, the Journal of Natural Products . Lectures were followed by parallel symposia dedicated to specialized areas of natural products research, such as genome mining for natural products discovery, chemistry of symbiosis, and drug discovery.